The Influence of Work Stress, Compensation and Organizational Culture on Work Productivity of Alfamidi Employees during the Covid-19 Pandemic: Pengaruh Stres Kerja, Kompensasi dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan Alfamidi di Masa Pandemi Covid-19 - Armansyah, Muhammad Ilham; Adji, Kumara (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of work stress, compensation and organizational culture on Alfamidi's work productivity in the city of Sidoarjo, Porong and Candi sub-districts during the covid-19 pandemic. This research is a descriptive study using quantitative methods. Data collection technique is by distributing questionnaires to 30 respondents who are Alfamidi employees in Porong and Candi sub-districts. The analytical technique used in this study is multiple linear regression using SPSS (statistical program for social science) version 21 for windows. The results of this study indicate that work stress variables affect productivity, compensation affects work productivity, and organizational culture variables do not effect on work productivity in the districts of Porong and Candi.